PENGGUNAAN PLATFORMANDROID UNTUK MENINGKATKAN PERDAGANGAN KELAPA DIMASA PANDEMI - Kasmi Kasmi; Siti Rohayati; Muhamad Muslihudin (Jurnal Signaling, 2021)
The use of technology in agriculture or in terms of assisting the state in helping to increase the trade-in coconut commodities can be very helpful, especially for those of the lower class who have commodity trading businesses. Small traders and natural coconut collectors marketed coconut commodities during the Covid-19 pandemic. During the pandemic, commodity prices soared but in terms of marketing, it was still not efficient, especially in small villages. So it can be expected that with this research an application system is built. can help coconut traders promote and market commodities more efficiently with a wider reach. The method used in designing application systems is the waterfall method, which uses the Java programming language in designing applications that are more efficient. The types of payment methods that can be done can use the method by credit card or in cash where consumers can also directly review the place. With this transaction, consumers can have more confidence in the quality of the commodities presented and can establish a relationship with the business owner directly. already done using an Android-based trading application showing the application can run well with the payment methods provided with product promotion features that can be reviewed directly by the buyer.